The finite element method for fluid dynamics - Zienkiewicz, O. C. (Elsevier Butterworth-Heinemann, 2005)
Dealing with general problems in fluid mechanics, convection diffusion, compressible and incompressible laminar and turbulent flow, shallow water flows and waves, this is the leading text and reference for engineers working with fluid dynamics in fields including aerospace engineering, vehicle design, thermal engineering and many other engineering applications. The new edition is a complete fluids text and reference in its own right. Along with its companion volumes it forms part of the indispensable Finite Element Method series. New material in this edition includes sub-grid sca.
"In the present edition we retain the three volume format of the fifth edition but have decided not to pursue the course of having three contiguous volumes -- rather we treat the whole work as an assembly of three separate works, each one capable of being used without the others ... The first volume is renamed The Finite Element Method: Its Basis and Foundamentals ... In [the second] volume we consider more advanced problems in solid and structural mechanics while in a third volume we consider applications in fluid dynamics"--Preface
Previous edition: 2000.